Sierra Leone After the End of the Armed Conflict - Zack-Williams, Alfred B. (2016)
Since March 1991, Sierra Leone has experienced continuous civil strife culminating in a protracted civil war, leading to widespread destructions of infrastructures and property, and the death of thousands of people, many more injured and over half of the population displaced. Three peace accords were signed in 1996, 1997 and 1999 in Abidjan, Conakry and Lame respectively. However, these agreements did not bring peace. In this paper, the author situates the reasons and the nature of the conflict, the events leading to both government and rebel leaders declaring in January 2002 the end to conflict. Finally, he looks at Sierra Leone following the formal declaration of an end to the war.